2020
DOI: 10.1103/physrevapplied.13.024053
|View full text |Cite
|
Sign up to set email alerts
|

Highly Tunable Nonlinear Hall Effects Induced by Spin-Orbit Couplings in Strained Polar Transition-Metal Dichalcogenides

Abstract: Recently, signatures of nonlinear Hall effects induced by Berry curvature dipoles have been found in atomically thin 1T'/T d -WTe2. In this work, we show that in strained polar transition-metal dichalcogenides(TMDs) with 2H-structures, Berry curvature dipoles created by spin degrees of freedom lead to strong nonlinear Hall effects. Under easily accessible uniaxial strain of order ∼ 0.2%, strong nonlinear Hall signals, characterized by Berry curvature dipole in the order of ∼ 1Å, arise in electron-doped polar T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(27 citation statements)
references
References 42 publications
1
25
0
1
Order By: Relevance
“…B is allowed by symmetry in noncentrosymmetric crystals and surfaces having certain point groups (see below). For example, in materials with a polar axis, large B has been found due to the presence of tilted Dirac or Weyl points in the band structure (6,(27)(28)(29)(30)(31)(32)(33)(34)(35). When B is nonzero and in the presence of an applied electric field, the imbalance in the probability of occupation f (k) = f (−k) leads to a net Berry curvature, which then induces a second-order anomalous current in the transverse direction.…”
Section: Significancementioning
confidence: 99%
“…B is allowed by symmetry in noncentrosymmetric crystals and surfaces having certain point groups (see below). For example, in materials with a polar axis, large B has been found due to the presence of tilted Dirac or Weyl points in the band structure (6,(27)(28)(29)(30)(31)(32)(33)(34)(35). When B is nonzero and in the presence of an applied electric field, the imbalance in the probability of occupation f (k) = f (−k) leads to a net Berry curvature, which then induces a second-order anomalous current in the transverse direction.…”
Section: Significancementioning
confidence: 99%
“…Unlike the anomalous Hall effect in the linear-response regime [3][4][5][6][7][8][9][10][11][12][13][14][15], the nonlinear anomalous Hall effect (NLAHE) does not require broken time-reversal symmetry (TRS) but needs inversion symmetry (IS) breaking. The Berry curvature dipole (BCD), which is defined as the first-order moment of the Berry curvature over the occupied states, is found to be responsible for NLAHE [16][17][18][19][20][21]. The importance of electron-electron interactions for the external magnetic field dependence of the nonlinear conductivities has been pointed out [22,23].…”
mentioning
confidence: 99%
“…(Throughout this work, we consider transport in the absence of magnetic field.) Nevertheless, when the inversion symmetry is broken, there could be a second-order Hall response [8][9][10][11][12][13][14][15][16][17]. Sodemann and Fu [8] showed that one contribution to this effect can be attributed to the dipole moment of Berry curvature over the occupied states.…”
Section: Introductionmentioning
confidence: 99%